Interview with Marc Prensky on Digital Natives and AI Natives: Reframing and Empowering 21st Century Kids - Gülden Demir (Yeni Medya)
On January 8, 2024, as part of the career planning course event, we conducted an online interview with author and educational writer Marc Prensky regarding his new article "Our Coming AI Natives." During our conversation with Prensky, renowned for introducing the concepts of "digital natives" and "digital immigrants," we explored the transformative potential of generative AI. Prensky provided insightful definitions of digital natives and AI natives, emphasizing the innate familiarity and adaptability of younger generations to digital tools and emerging AI technologies.